First Report of the Flowering of Phyllostachys Bambusoides Sieb. et Zucc. in Sikkim with a Note on its Allied Species - Majumder, R. B.; Majumdar, N. C.; Banerjee, R. N. (Indian Forester, 1985)
no abstract